Analisis Pengaruh Jarak dan Posisi Lubang Rivet Sambungan Tumpuk Terhadap Kekuatan dan Faktor Keamanan - Aldi Tio Nugraha (Peneliti.net, 2023)
Connection with plates by stacking them using rivets is generally used in construction or machine parts that have different materials. Failures that occur in these connections are generally in the plate holes that are connected to one another. The vertical or horizontal distance of the hole diameter that does not match is the cause of the failure. From the research I conducted on the pile connection model using the Ansys application, it is known that the plate riveted connection with an axial load of 20 N. The riveted stack connection will be safe at the distance between vertical holes L = 32 mm and horizontal C = 32 mm. The stress that occurs at 275.75 MPa is much smaller than at other distances. In terms of the factor of safety that occurs for the distances L and C mentioned above, it gives a safe value of 1.37.